Research on Injury Disparities: A Scoping Review - Megan Moore; Kelsey M. Conrick; Molly Fuentes; Ali Rowhani-Rahbar; Janessa M. Graves; Divya Patil; Madeline Herrenkohl; Brianna Mills; Frederick P. Rivara; Beth Ebel; Monica S. Vavilala (Mary Ann Liebert, 2019)
Background: Research on disparities in traumatic injury has not been well characterized, limiting understanding of gaps in research and development of successful interventions. We conducted a scoping review to identify and synthesize research on disparities in intentional and unintentional traumatic injuries. Methods: The review was guided by PRISMA Extension for Scoping Reviews. PubMed, PsycINFO, Web of Science, and CINAHL and systematic reviews from 2007 to 2017 were searched. Eligible articles were peer reviewed; conducted in the United States; and reported on clearly defined physical trauma and disparity, defined by Cochrane PROGRESS-Plus criteria. One reviewer assessed article titles and a second reviewer validated the inclusion with a random sample. Abstract and full-text review by two reviewers determined final inclusion. Results: Of 7382 unique articles screened, 653 articles were included; inter-rater agreement was high (K=0.995). Studies reported on disparities in the acute hospital setting (104) or postacute/rehabilitation (86), with fewer focused on prevention (57) and policy development (6). Research methods used were quantitative (593) with 25 intervention studies, qualitative (45), qualitative/quantitative (7), and community-based participatory research (8). Age ranges of included studies were all ages (124), adults (318), pediatric/youth/adolescents (172), and older adults (40). Racial disparities were most commonly measured (439 studies); 38 created a white/nonwhite binary. Other commonly measured disparities were place of residence (122), insurance (111 studies), gender (89), age (75), and socioeconomic status measures (61). Disparities were noted in all of the categories. Studies commonly aggregated all types of traumatic injuries (129) or all types of violence (105). Conclusions: The extant injury literature lacks research on prevention and policy to address disparities. Many studies aggregated types of trauma and patient groups, preventing an understanding of distinctions between groups and potential interventions. Intervention and community-based research strategies were limited. Future research can better specify measurement of understudied equity categories, trauma types and intent, and racial groups.